A interação entre avaliação interna e planejamento estratégico na Universidade Federal de Santa Maria - Castellanelli, Luise Medina Cunha (2018)
This study investigates the relation between the processes of internal evaluation and strategic planning in the Federal University of Santa Maria (UFSM), in order to verify the possibility of using the internal evaluation surveys currently applied by the Self Evaluation Committee (CPA) to measure the institutional results according to the goals outlined in the current Institutional Development Plan (PDI). The theoretical framework of the study includes three main topics: the evaluation of Higher Education Institutions (HEI) under the New Public Management theory, strategic planning in universities and, finally, the need for alignment of the processes of strategic planning and evaluation within HEI. The historical evolution and the current situation of the internal evaluation and strategic planning processes in UFSM were also presented in order to contextualize the study. Regarding the research strategy, the method was the case study with a qualitative approach. In order to achieve the main goal of the research, a temporal investigative line was drawn to verify the alignment of certain aspects of both processes in the past and in the present, thus allowing the exploration of the future scenarios. To verify how the internal evaluation supported the creation of the PDI 2016-2026, the method applied was the documentary analysis. As the result of this analysis, it was not possible to establish if the internal evaluation process was in fact considered during the construction of the document. To verify the alignment of the questions of surveys that are currently being applied by the CPA and the strategic goals of the PDI 2016-2016, the method chosen was the focus group supported by the content analysis of the strategic goals to easy the association with the questions. At this stage, it was possible to verify that overall the questions can be linked to the objectives, although some of them cannot be measured by self-evaluation surveys. The lack of integration between the processes during the construction of the PDI 2016-2026 was identified as one of the possible causes for the superficiality of the relations found at this stage. The focus group then gathered a second time to explore the future scenarios for the alignment of the processes of strategic planning and internal evaluation. The group concluded that the surveys could be used to measure institutional performance according to strategic goals without the need of other significant changes if some specific topics were to be included. The result of the study is an outline of the questions to be included in the surveys according to the topics suggested by the focus group.